Wellbore Temperature and Pressure Field in Deep-water Drilling and the Applications in Prediction of Hydrate Formation Region - Sun, Wantong; Wei, Na; Zhao, Jinzhou; Zhou, Shouwei; Zhang, Liehui; Li, Qingping; Jiang, Lin; Zhang, Yao; Li, Haitao; Xu, Hanming; Li, Cong; Shen, Xuncheng; et al. (Frontiers in Energy Research, 2021)
In the process of deep-water drilling, gas hydrate is easily formed in wellbore due to the environment of low temperature and high pressure. In this study, A new, systematic and accurate prediction method of temperature, pressure and hydrate formation region in wellbore is developed. The mathematical models of wellbore pressure and transient heat transfer are established, the numerical solution method based on fully implicit finite difference method is developed, and the accuracy is verified by comparing with the field measured data. Combined with hydrate phase equilibrium model, the hydrate formation region in wellbore is predicted, and the sensitivity effects of nine factors on wellbore temperature, pressure and hydrate formation region are analyzed. Finally, the influence regularities and degree of each parameter are obtained. The increases of circulation time, geothermal gradient, displacement of drilling fluid and injection temperature will inhibit the formation of hydrate in wellbore, and the influence degree increases in turn; the increases of wellhead backpressure and seawater depth will promote the formation of hydrate in wellbore, and the influence degree increases in turn; the changes of drilling fluid density, well depth and hole deviation angle have little effect on the formation of hydrate in wellbore.